Mapping the Scholarly Landscape: A Bibliometric Analysis of Female Muslim Influencers and Digital Piety on Social Media 2018-2024 - Zakiyyah Wardatul Laini; Siti Misbah; Desi Firmasari; Fransiskus Novrianto Pakpahan (Tinta Emas Publisher, 2023)
This study provides a comprehensive bibliometric analysis of the emerging research field examining female Muslim influencers and the construction of digital piety on social media. Using Scopus data from 2018 to 2024 and analytical tools including VOSviewer, we mapped the intellectual structure and thematic evolution of this domain through co-occurrence and co-citation analyses. The findings reveal a rapidly consolidating field organized around five key thematic clusters: platform-specific studies (TikTok, Instagram), methodological approaches (digital ethnography), and conceptual foci (visual authority, influencer culture). Co-citation analysis further identified the field's foundational pillars, integrating theories of the Islamic public sphere, ethnographic studies of Muslim femininity, and critical frameworks of digital labor. While the research demonstrates increasing scholarly coherence, our analysis identifies significant gaps, including platform-centric fragmentation and under-explored political economy dimensions. The study concludes by proposing a structured research agenda advocating for cross-platform analyses, comparative geographical studies, and critical investigations into the commodification of religious expression. This bibliometric mapping not only synthesizes the current state of knowledge but also provides a strategic roadmap for future scholarship in this dynamically evolving field at the intersection of digital media, gender studies, and contemporary Islamic practice.